2015
DOI: 10.1002/ijc.29400
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work, chronotype and prostate cancer risk in the MCC‐Spain case‐control study

Abstract: Night shift work has been classified as a probable human carcinogen based on experimental studies and limited human evidence on breast cancer. Evidence on other common cancers, such as prostate cancer, is scarce. Chronotype is an individual characteristic that may relate to night work adaptation. We evaluated night shift work with relation to prostate cancer, taking into account chronotype and disease severity in a population based case-control study in Spain. We included 1,095 prostate cancer cases and 1,388 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
151
3
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 48 publications
9
151
3
5
Order By: Relevance
“…For example, the risk to develop breast cancer was extensively increased in nurses exposed to long-term rotating night shift work [6]. Similar results were obtained for prostate cancer risk in night shift workers [7]. Out of note, in 2007 an agency of the WHO has classified night shift work leading to circadian disruption as 'probably carcinogenic' to humans [8].…”
Section: Circadian Clock Disruption Is Associated With Cancermentioning
confidence: 73%
“…For example, the risk to develop breast cancer was extensively increased in nurses exposed to long-term rotating night shift work [6]. Similar results were obtained for prostate cancer risk in night shift workers [7]. Out of note, in 2007 an agency of the WHO has classified night shift work leading to circadian disruption as 'probably carcinogenic' to humans [8].…”
Section: Circadian Clock Disruption Is Associated With Cancermentioning
confidence: 73%
“…In the present study, we did not find differences in sunlight exposure between day and night workers. 3 Similarly in a recent nested case-control study, night shift workers reported more frequent sun exposure than those with day work, that often spend most of the daytime hours working indoors. 5 More data are needed on sun exposure and vitamin D levels among current and past night workers, in order to confirm if this biologically plausible hypothesis can explain part of the increased risk for prostate cancer observed among night shift workers.…”
mentioning
confidence: 90%
“…3 We assessed present and past sun exposure summer habits through a questionnaire, as proxies for vitamin D levels at least for the brightest months of the year, although we agree that it would have been preferable if more details (e.g., unbathing, protection cream) were available. All models were adjusted for past sun exposure that was not a major confounder of the night shift work-prostate cancer association.…”
mentioning
confidence: 99%
“…Dear Sir, With interest we read the thought-provoking case-control study by Papantoniou et al 1 into night shift work and prostate cancer risk. We compliment the authors for employing chronotype information in their analyses as a means to capture the endogenous propensity to be awake and asleep.…”
mentioning
confidence: 99%
“…4 Our suggested definition of a CD metric 4 fills the gap how "shift work that involves circadian disruption" may be defined and used in epidemiological studies, namely "as the split physiological nexus of internal and external times." 4,5 Papantoniou et al 1 stated that their "data suggest that night shift work that involves circadian disruption may be associated with cancer promotion and therefore decreased survival." From our point of view, the authors analysed "night shift work" but not necessarily "night shift work that involves circadian disruption."…”
mentioning
confidence: 99%